Influences of Human Cognition and Visual Behavior on Password Strength During Picture Password Composition - Katsini, Christina; Fidas, Christos; Raptis, George E.; Belk, Marios; Samaras, George; Avouris, Nikolaos (Proceedings of the 2018 CHI Conference on Human Factors in Computing Systems, 2018)
Visual attention, search, processing and comprehension are important cognitive tasks during a graphical password composition activity. Aiming to shed light on whether individual differences on visual behavior affect the strength of the created passwords, we conducted an eye-tracking study (N=36), and adopted an accredited cognitive style theory to interpret the results. The analysis revealed that users with different cognitive styles followed different patterns of visual behavior which affected the strength of the created passwords. Motivated, by the results of the first study, we introduced adaptive characteristics to the user authentication mechanism, aiming to assist specific cognitive style user groups to create more secure passwords, and conducted a second study with a new sample (N=40) to test the adaptive characteristics. Results strengthen our assumptions that adaptive mechanisms based on users' differences in cognitive and visual behavior uncover a new perspective for improving the password's strength within graphical user authentication realms.
Keywords: cognitive styles; cued-recall authentication; eye-tracking; field dependence-independence; graphical user authentication; picture passwords; usable security; visual behavior